Correlation of community characteristics with ecoprint's expertise in supporting a more sustainable Bukit Barisan Selatan National Park - Niken aurora iwais; Christine Wulandari; Tadzkia Shalihah Sauce; Yuda Ferdiawan; Aldina Refa Vernanda; Achmad Haris; Farhad Maryan Saputra (Talenta Publisher, 2026)
The buffer area of the Bukit Barisan Selatan National Park (BBSNP) has the potential to be developed through the creative economy, including ecoprint. Ecoprint is one of the textile dyeing techniques that uses natural materials, making it environmentally friendly and having artistic and economic value. This study aims to analyze the social characteristics of the BBSNP community, the level of ecoprint skills, and the relationship between the two in supporting regional Sustainability. The research uses quantitative methods through questionnaires that are analyzed descriptively and analytically. The results of the study show that the productive age group dominates the community, secondary education is common, farming is common, and the community has a good environmental experience. Ecoprint skills are at the basic to intermediate level and contribute as an additional income. The study also found that environmental experience and social engagement were more influential on ecoprint skills. Community empowerment through ecoprint training has been proven to foster new skills, build creativity, and strengthen collaboration between the government, academics, and business actors. Thus, ecoprints not only have aesthetic value but also serve a strategic role in supporting a creative economy based on local wisdom and environmental conservation